Early effect of intra-arterial treatment in ischemic stroke on aphasia recovery in MR CLEAN. (31st May 2016) - Crijnen, Yvette S.; Nouwens, Femke; de Lau, Lonneke M.L.; Visch-Brink, Evy G.; van de Sandt-Koenderman, Mieke W.M.E.; Berkhemer, Olvert A.; Fransen, Puck S.S.; Beumer, Debbie; van den Berg, Lucie A.; Lingsma, Hester F.; Roos, Yvo B.W.E.M.; van der Lugt, Aad; et al.
Abstract : Objective: To investigate the effect of intra-arterial treatment (IAT) on early recovery from aphasia in acute ischemic stroke. We hypothesized that the early effect of IAT on aphasia is smaller than the effect on motor deficits. Methods: We included patients with aphasia from the Multicenter Randomized Clinical Trial of Endovascular Treatment for Acute Ischemic Stroke in the Netherlands (MR CLEAN), in which 500 patients with a proximal anterior circulation stroke were randomized to usual care plus IAT (<6 hours after stroke, mainly stent retrievers) or usual care alone. We estimated the effect of IAT on the shift on the NIH Stroke Scale (NIHSS) item language and the NIHSS item motor arm at 24 hours and 1 week after stroke with multivariable ordinal logistic regression as a common odds ratio, adjusted for prognostic variables (acOR). Differences between the effect of IAT on aphasia and on motor deficits were tested in a multilevel model with a multiplicative interaction term. Results: Of the 288 patients with aphasia, 126 were assigned to IAT and 162 to usual care alone. The acOR for improvement of language score at 24 hours was 1.65 (95% confidence interval [CI] 1.05–2.60), and at 1 week 1.86 (95% CI 1.18–2.94). The acOR for improvement of motor deficit at 24 hours was 2.44 (95% CI 1.54–3.88), and at 1 week 2.32 (95% CI 1.43–3.77). The effect of IAT on language deficits was significantly different from the effect on motor deficits at 24 hours and 1 week ( p = 0.005 and p = 0.011). Conclusions: IAT results in better early recovery from aphasia than usual care alone. The early effect of IAT on aphasia is smaller than the effect on motor deficits. Classification of evidence: This study provides Class II evidence that for patients with acute ischemic stroke IAT increases early recovery from aphasia and that the early effect on aphasia, as measured by the NIHSS, is smaller than the effect on motor deficits.